Evaluation of the domestic solid waste management system of Guihulngan, Negros Oriental, Philippines - Ga, Filipinas V.
The municipality of Guihulngan is a growing community in the Province of Negros. It is confronted with the problem of solid waste management which s exarcerbated by the meager resources of the local government and the many other concerns that compete for its attention and funds. Health conditions in the lowlands might be affected if evacuation of the upland people to the lowlands continues as a consequence of the peace and order problem in the mountains. Evaluation of the domestic solid waste management system was made in the context of the community's socio-economic, political and ecological conditions and domestic solid waste characteristics. Finding showed that it fell short of the charcteristics of a sound solid waste management system in terms of ecological soundness, sustainability in the political context, and economic viability.. The community's domestic wastes were highly organic, 76.1% by weight and 68.9% by volume. Household management was largely by dumping within their own premises, vacant lots or the coastal areas, and by burning especially those in barangays unserved by the present solid waste collection system. Sixty five to ninety four percent of the households were not segregating their wastes. Economics drone some to reuse glass and plastic containers and thin plastic bags whenever condition warranted. Glass bottles were sold to junk dealers but other recyclable materials that had no local market were dumped altogether. The local government's collection system served only 25% of the households in Barangay Poblacion, the urban center of municipality. Twelve to fourteen cubic meters of wastes collected daily ended up in a leased open dumpsite in Barangay Malusay, about three kilometers from the Poblacion and currently, the subject of complaint from the neighborhood. In the year 2002, the local government allocated over Php683,000 for soild waste management. The municiapl ordinance provision that each household pays a garbage fee of Php 50.00 anually has not been implemented. Only commercial establishments paid Php 120 annually. These fees covered only 3% of the collection and disposal costs of the system. The whole system has been operating under subsidy. Subsidies send wrong signals to generators that wastes are not their responsibility and accountability. They do not encourage waste reduction, reuse nor recycling nor a change in attitude and behavior of the generators. The ultimate goal of a solid waste management system is a reduction in wastes geerated and disposal and the promotion of the use of waste materials as resources in environmentally sound and sustainable manner.